Couples' Relationship Qualities and Child Behavior Problems - Lovett, Erin Wallace (2020)
ABSTRACT This dissertation examines couples’ relationship quality on child externalizing behavior problems. Family systems theory and Belsky’s determinants of parenting model posit that child behavior problems stem from problematic familial relationships and lack of support within the couple’s relationship. A secondary data analysis was conducted using data from the National Fragile Families and Child Wellbeing Study. The independent variables represent couples’ relationship quality and are affection/support, relationship instability, and coercion. Dependent variables represent child behavior problems and are aggression measured when children are age five and age nine, and rule-breaking behavior when the child is age nine. To examine what relationship qualities between couples might impact child aggression or rule-breaking behavior, twelve multiple regression analyses were run yielding a sample range of 768 to 907 focal children and their biological parents. The findings from this study suggest that there are strong, consistent relationships between parents’ reports of affection and support and child externalizing behavior problems. Thus, the evidence taken from these findings indicates that problems with affection and support in couples’ relationships are an important risk factor for the development of children's externalizing behavior problems. Father reports of coercion were found to be significantly associated with child rule-breaking behavior at age nine. Maternal depression was significantly associated with child aggression at ages five and nine in both maternal and paternal regression models. Implications for future social work research and practice are discussed